Sutureless biological self-adhesion matrix lens thickened cornea and preparation method and application thereof
By introducing oxidized chondroitin sulfate and the fourth generation of dendritic macromolecular polyamide-amine on the surface of the corneal matrix lens, the self-adhesion of the corneal matrix lens is achieved by using electrostatic tangling reaction, and the existing bioadhesive agents in the corneal matrix lens are solved. The problems of poor adhesion, poor stability and low light transmittance in seamless transplantation have achieved custom thickening of the cornea and seamless transplantation, and reduced postoperative inflammatory response.
Patent Information
- Application Number
- CN202411693509.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
AI Technical Summary
Existing bioadhesive agents have problems such as poor adhesion, poor long-term stability and low light transmittance in corneal stromal lens seamless transplantation, which is difficult to meet the needs of deep corneal transplantation.
By introducing oxidized chondroitin sulfate and the fourth generation of dendritic macromolecular polyamide-amine on the surface of the corneal matrix lens, the self-adhesion of the corneal matrix lens is achieved by using the electrostatic entanglement reaction between the macromolecules to achieve self-adhesion of the corneal matrix lens, forming a strong cohesion and adhesion strength planting.
Custom thickening and seamless transplantation of corneal stromal lenses are achieved, which improves long-term stable adhesion ability, maintains high light transmittance, and reduces postoperative inflammatory response.
Smart Images

Figure CN119455126A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and relates to a medical corneal material, in particular to a sutureless biological self-adhesive matrix lens thickened cornea, and a preparation method and application thereof. Background Art
[0002] The corneal stromal lens removed by femtosecond laser small incision lenticule extraction (SMILE) has the advantages of easy material acquisition, wide source and low immunogenicity. It can be used to correct hyperopia and presbyopia, repair corneal ulcer perforation, and treat corneal defective lesions, effectively alleviating the current shortage of corneal donors.
[0003] However, the thickness of the corneal stromal lens obtained by the above surgical methods is often thin. The thickness of the SMILE corneal stromal lens is about 60 to 150 μm. For diseases such as deep corneal ulcers and perforations, the thickness of the transplanted lens graft needs to be 300-400 μm. It is difficult to completely repair a single-layer corneal stromal lens.
[0004] In order to transplant lenses for deep corneal diseases, the traditional treatment method is mainly to suture multiple corneal stromal lenses with surgical sutures. However, this suturing method is time-consuming and technically demanding, and due to the poor biocompatibility of the sutures, a series of suture foreign body reactions may occur. In addition, due to the large deformation of the surrounding tissues by the sutures, it is easy to cause iatrogenic ocular surface high astigmatism, thereby causing decreased vision. In the face of this problem, the use of adhesives is an attractive alternative to sutures.
[0005] Related studies have pointed out that biological adhesives can replace corneal sutures in corneal lens transplantation. Among them, cyanoacrylate and fibrin glue are the two most common tissue adhesives in ophthalmology. However, although cyanoacrylate has high bonding strength, due to its toxicity and poor transparency, if it is used as a biological adhesive for seamless transplantation of corneal stroma lenses, there will be factors such as safety and problems affecting transparency. Therefore, it is not recommended for corneal transplantation clinically. Another adhesive, fibrin glue, has been used in various eye surgeries, such as as a corneal transplant adhesive for the treatment of corneal perforation, ocular surface diseases and glaucoma, but current studies have found that fibrin adhesives have low bonding strength and a fast degradation rate, and cannot achieve long-term stable bonding, which limits its application in deep corneal transplantation.
[0006] Therefore, the following problems still exist in the use of corneal stromal lenses for transplantation to treat deep corneal diseases: (1) The use of sutures to fix the corneal graft in corneal lens transplantation is prone to various complications. The use of sutures for transplantation is not only time-consuming and requires a high level of surgical skills, but is also associated with many potential complications after corneal transplantation, including infectious keratitis, corneal neovascularization, and high astigmatism. (2) When using suture-free surface mirror technology for transplantation, the stability of the corneal lens graft is poor due to the influence of mechanical external forces such as blinking and tears, and it is easy to slip off. (3) The thickness of the corneal stromal lens is relatively thin. The thickness of the SMILE corneal stromal lens is about 60 to 150 μm, while for diseases such as deep corneal ulcers and perforations, the thickness of the transplanted lens graft needs to be 300-400 μm. It is difficult to completely repair a single-layer corneal stromal lens, and the biological adhesives used in the seamless technology between multiple corneal stromal lenses currently generally have weak adhesion, poor long-term stability, and low transparency.
[0007] Therefore, in order to facilitate the clinical application of corneal stromal lens transplantation, it is very important to develop a corneal graft with customizable thickness and the ability to achieve rapid and effective adhesion to repair deep corneal defects while avoiding tissue damage.
[0008] Based on this, the following conditions must be met for suture-free corneal lens transplantation: 1) Good self-adhesion to overcome the slippage of the implant caused by external mechanical forces such as blinking; 2) The corneal surface is covered with tears, and it must have strong adhesion to wet tissue without sutures; 3) In order to meet the needs of deep corneal defect repair, the corneal implant needs to have a certain thickness (300-400μm); 4) The corneal implant needs to have good light transmittance and not affect the refractive index of the cornea. However, how to ensure the long-term stable adhesion between the corneal stroma lens units of the corneal implant and the characteristics of high light transmittance is still a technical problem that needs to be solved urgently in clinical practice.
[0009] For example, patent document CN 103892938 A discloses a corneal lamellar sheet, which is formed by stacking corneal stromal lens units, and each corneal stromal lens unit is bonded with a fibrin adhesive, and the maximum thickness of the obtained corneal lamellar sheet can reach 350-450 μm. However, since the corneal stromal lens units are bonded with a fibrin adhesive, the bonding strength is low, the bonding between the stromal lens units is prone to fall off, and the bonding stability cannot be maintained for a long time, and the light transmittance of the adhesive is not high.
[0010] For example, patent document CN 108883207 A discloses a dendrimer-bioadhesive polymer hydrogel nano glue, which is prepared by combining dendrimer molecules with bioadhesive polymers and cross-linking to form corneal tissue that can be used to eliminate corneal inflammation. Although the hydrogel nano glue has good adhesion in a short period of time, its long-term adhesion stability is insufficient, and its stability is poor when it is used for bonding between multiple corneal stromal lens units. On the other hand, the gel nano glue prepared by the patent document method needs to be cross-linked by UV light, but UV ultraviolet light is more harmful to the eyes, so it is not suitable for corneal transplantation surgery; and the patent method triggers free radical cross-linking by light to form a gel system, which still belongs to glue bonding. Similar to the above-mentioned biological glue, it cannot achieve self-assembly suturing between multiple corneal stromal lenses, and the physical barrier of its gel layer leads to poor light transmittance of the thickened corneal stromal lens after bonding.
[0011] Previous studies have used photocurable hydrogels composed of methacryloyl gelatin (GelMA) and oxidized dextran (ODex) to achieve sutureless in situ fixation of lamellar corneal grafts, but the adhesive hydrogels show limited wet adhesion, and the curing process is usually accompanied by the use of harmful cross-linking reagents or the release of toxic by-products. They also have a short degradation cycle, poor postoperative stability, and may leave residues on the tissue, making it impossible to achieve long-term stable adhesion and transplantation.
[0012] Therefore, developing a device with good adhesion, capable of self-assembly bonding between multiple corneal matrix lens units, capable of stable adhesion for a long time, and having high light transmittance, so that it can be used as a good substitute for corneal tissue implantation, especially for deep corneal transplantation, has become a technical problem that needs to be solved urgently. Summary of the invention
[0013] The present invention is to solve the above technical problems, thereby providing a sutureless biological self-adhesive matrix lens thickened cornea and its preparation method and application. The technical purpose of the present invention is to solve the problems that the existing biological adhesive has poor adhesion between the corneal matrix lens units, poor long-term stability, and poor light transmittance after adhesion and compounding by biological glue, which cannot be well used for the preparation and transplantation of thickened cornea.
[0014] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:
[0015] The present invention first provides a method for preparing a cornea thickened by a sutureless bio-self-adhesive matrix lens, comprising the following steps:
[0016] (1) soaking a corneal stromal lens unit in an oxidized chondroitin sulfate solution to obtain a corneal stromal lens modified with oxidized chondroitin sulfate;
[0017] (2) treating another corneal stromal lens unit by immersion in a fourth-generation dendrimer polyamide-amine solution to prepare a G4 PAMAM-modified corneal stromal lens;
[0018] (3) The two corneal stromal lens units obtained in step (1) and step (2) are stacked to achieve self-adhesion through the electrostatic entanglement reaction between molecules, thereby obtaining the seamless biological self-adhesive stromal lens thickened cornea.
[0019] When preparing seamless thickened cornea, existing bioadhesives generally have poor adhesion, cannot achieve long-term stable adhesion, and have poor transmittance due to the barrier layer formed by the bio-glue. In order to improve the bioadhesion between tissues, the present invention creatively uses the electrostatic entanglement between macromolecules to successfully achieve the preparation of a seamless thickened corneal stroma lens with biological self-adhesion, greatly improving its long-term stable adhesion ability. At the same time, since different corneal stroma lenses are not adhered to each other by bio-glue, but self-adhesion is achieved by electrostatic entanglement between molecules, which well solves the problem of low transmittance of thickened cornea.
[0020] The present invention realizes the formation of ionic complexes between polyanions and polycations at the interface through the above-mentioned treatment method, so that intricate entanglement and interlocking effects are generated between tissues, thereby achieving highly tight adhesion between tissues at the microscopic level, which has the characteristics of rapid response speed and no residue. The bonding method of the macromolecules electrostatically entangled at the tissue interface can achieve a high degree of biological adhesion, which well solves the problems of poor adhesion and insufficient long-term adhesion stability of existing bioadhesives.
[0021] The method provided by the present invention is to introduce a large amount of anions -SO3 - Oxidized chondroitin sulfate (O-CS) with cation -NH3 + The macromolecule G4PAMAM of the group successfully undergoes an electrostatic entanglement reaction between two corneal stromal lens units, successfully forming a corneal stromal lens implant with strong cohesion and adhesion strength on a molecular scale, thereby achieving customized thickening of the cornea and sutureless transplantation, providing the possibility of repairing deep corneal defects. This intermolecular electrostatic entanglement reaction enhances the self-adhesion force (33.80±2.12kPa) of the corneal stromal lens, and the modified corneal stromal lens still has good light transmittance (70% to 73%) and excellent biocompatibility, which is conducive to achieving long-term stable adhesion. However, the corneal stromal lenses obtained by the several bonding methods attempted in the comparative examples of the present invention either have insufficient adhesion or poor light transmittance.
[0022] On the other hand, G4 PAMAM macromolecules can also encapsulate and release drugs slowly, which has additional functions such as inhibiting postoperative inflammatory response and promoting repair. By implanting the self-adhesive thickened corneal lens into the rabbit corneal defect model, the deep corneal defect area was successfully repaired. One month after the operation, the implanted lens remained transparent, without displacement, and there was no significant difference in corneal thickness compared with the undamaged rabbit cornea, and epithelial remodeling was completed 7 days after the operation, which promoted the repair process after transplantation. It was further verified by immunofluorescence that the expression of inflammatory-related factors CD11b, Ly6g and fibrosis-related factors α-SMA in corneal tissue after transplantation was not significantly different from that in the normal control group, which effectively alleviated the postoperative inflammatory response. Therefore, the tissue self-adhesion method based on electrostatic entanglement between macromolecules provided by the present invention can realize seamless transplantation between tissues, providing a new idea for living tissue transplantation or wound repair.
[0023] Furthermore, the concentration ratio of the oxidized chondroitin sulfate to the fourth-generation dendrimer polyamide-amine is 2:1.
[0024] Furthermore, the concentration of the oxidized chondroitin sulfate solution in step (1) is 1 mg / mL.
[0025] Furthermore, the concentration of the fourth-generation dendrimer polyamide-amine solution in step (2) is 0.5 mg / mL.
[0026] Furthermore, the source of the corneal stromal lens is the corneal stromal lens discarded as medical waste generated by femtosecond laser small incision corneal stromal lens removal surgery.
[0027] Furthermore, the oxidized chondroitin sulfate is prepared by treating chondroitin sulfate with sodium periodate.
[0028] The second object of the present invention is to provide a sutureless bio-self-adhesive matrix lens for thickening the cornea obtained by the preparation method as described above.
[0029] Furthermore, the sutureless bio-self-adhesive matrix lens of the present invention thickens the cornea to a thickness of 100-400 μm.
[0030] Furthermore, the sutureless bio-self-adhesive matrix lens thickened cornea of the present invention has a light transmittance of 70-73%.
[0031] The third object of the present invention is to provide the use of the above-mentioned sutureless bio-self-adhesive matrix lens thickened cornea as a corneal tissue engineering material for repairing deep corneal defects.
[0032] The beneficial effects of the present invention are as follows:
[0033] The present invention introduces a large amount of anion -SO3 on the surface of the corneal stroma lens -Oxidized chondroitin sulfate (O-CS) and cation -NH3 + The macromolecule G4 PAMAM of the group undergoes electrostatic entanglement reaction, NH3 + and SO3 - Through the macromolecular electrostatic entanglement mechanism, entanglement occurs between the lens interface and with polar groups on the cornea (such as -COOH and -NH2), thereby achieving customized corneal thickening and sutureless transplantation. In addition, G4 PAMAM can be used to encapsulate and release drugs, thereby constructing a customized corneal stroma module that inhibits postoperative inflammatory response and promotes repair. In in vitro experiments, we explored the optimal concentrations of oxidized chondroitin sulfate and G4 PAMAM to take into account the actual application requirements of corneal tissue adhesion and transmittance (up to 73%), and verified the effects of chondroitin sulfate and G4 PAMAM on the physiological activity, collagen fiber structure and transparency of corneal stromal cells and corneal stromal lenses by cell culture, flow cytometry, immunofluorescence staining, etc. In the rabbit corneal defect model, the wound healing response after transplantation of the customized corneal stroma module was studied by slit lamp microscopy, anterior segment OCT and histopathological staining. We expect that this customized corneal stroma module can achieve sutureless repair of corneal defects or diseased tissue, reduce postoperative inflammatory response, and provide new ideas for living tissue transplantation or wound repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Preparation and characterization of the adhesive corneal stromal lens; (A) Schematic diagram of the synthesis of chondroitin sulfate (CS); (B) Attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy analysis of CS and the aldehyde functionality of CS (Ad-CS); (C) Rendering of the double-layer adhesive lens; (D) Scanning electron microscopy observation of the three-dimensional structure and physical morphology of the double-layer corneal stromal lens; (E) Characterization of the binding between oxidized chondroitin sulfate (O-CS) or (F) chondroitin sulfate and G4 PAMAM; (G) Quantitative analysis of rhodamine and (H) FITC fluorescence intensity; (I) Scanning electron microscopy images of the corneal stromal lens surfaces of each group.
[0035] Figure 2 In vitro cell compatibility of CS and G4; (A) Representative live / dead images of corneal stromal cells in each group after 1 day of culture, scale bar = 50 μm; (B) Flow cytometry analysis results of corneal stromal cells in each group after 1 day of culture; (C) Immunofluorescence staining images of ALDH3A1, Lumican, α-SMA and FN expression in cells of each group, scale bar = 50 μm; (D) Western blotting and (E) quantitative analysis results of cells of each group; (F) qPCR analysis results of cells of each group (*P<0.05, **P<0.01, ***P<0.001 and ****P<0.0001).
[0036] Figure 3 Figure 2 shows the biological properties and adhesion test of bio-self-adhesive matrix lenses with electrostatic entanglement of macromolecules; (A) Average transmittance of corneal matrix lenses modified with different CS and G4 PAMAM concentrations; (B) Three-dimensional structure and thickness of bio-self-adhesive thickened matrix lenses and single-layer corneal matrix lenses; (C) Live and dead staining photos of lenses in each group. Live cells and dead cells were incubated with Calcein-AM (live cells) and Ethidium homodimer-1 (dead cells) solutions, respectively, and the fluorescence intensity of live cells and dead cells in lenses in each group was quantitatively analyzed; (D) Phalloidin staining and quantitative analysis of lenses in each group; (E) Quantitative analysis of adhesion between corneal matrix lenses (*vs.Control; #vs.G4, *P<0.05, **P<0.01, ***P<0.001, ****P<0.0001).
[0037] Figure 4 Characterization and function of G4-Pu; (A) Macroscopically, the turbid G4-Pu suspension was transformed into a transparent G4-Pu aqueous solution; (B) SEM results of G4 PAMAM and G4-Pu; (C) Particle size results of G4 PAMAM and G4-Pu; (D) Zeta potential of G4 PAMAM and G4-Pu; (E) Formation of G4 PAMAM, 5-ASA and G4-Pu complex; (F) Drug release curve of G4-Pud using Pu as a model drug; (G) Adding different concentrations of puerarin to explore its effect on cell activity; (H) CCK8 analysis of the effect of puerarin on the proliferation ability of corneal stromal cells induced by LPS; (I) ELISA analysis of the expression of IL-6, IL-1β and TNF-a in the cell supernatant after LPS inflammatory cell model and culturing with puerarin; (J) Western blot analysis of IL-6, IL-1β and TNF-a in each group of cells.
[0038] Figure 5 In vivo rabbit eye model using self-adhesive thickened corneal lens transplantation to repair deep corneal stromal defects; representative (A) slit-lamp photographs and (B) OCT images immediately after surgery, 3 days, 1 week, 2 weeks, and 1 month after surgery; (C) comparison of corneal epithelial healing rate after transplantation, corneal wound surface stained with fluorescent dye and quantified under cobalt blue light; (D) corneal thickness and (E) corneal opacity after transplantation; *Compared with the corneal defect group.
[0039] Figure 6The following are histological analyses of corneal stromal defects in rabbits one month after surgery; (A) HE staining of healthy rabbit corneas and rabbit corneas after lens transplantation in each group (scale bar, 100 μm); (B) Masson staining of healthy rabbit corneas and rabbit corneas after lens transplantation in each group; (C) Fluorescent staining images of luminan (scale bar, 200 μm); (D) Fluorescent staining images of CD11b and Ly6g (scale bars, 200 μm and 40 μm); (E) Fluorescent staining images of α-SMA and COL1A1 (scale bar, 200 μm); (F) Quantitative analysis of fluorescent staining of luminan, (G) CD11b, (H) Ly6g, (I) α-SMA and (J) COL1A1. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.
[0041] Example 1
[0042] 1. Experimental Materials and Methods
[0043] 1. Human corneal stromal lens acquisition
[0044] Myopic patients who underwent SMILE surgery at the Fudan University Eye, Ear, Nose and Throat Hospital (Shanghai, China) from October 2022 to June 2023 were selected, and the discarded corneal stromal lens was removed during the operation for experimental research. The SMILE surgery used the VisuMax femtosecond laser platform (Carl Zeiss Meditec, Jena, Germany) with a repetition rate of 500kHz and a pulse energy of 130nJ. The thickness of the corneal cap was set to 120μm, and the lens optical zone was 6.2-6.8mm. The small incision position was set to 90° above and the length was 2mm. All SMILE surgeries were for myopia or myopic astigmatism correction treatment, and the patients were fully informed, and written informed consent was obtained from all patients. This study was approved by the Ethics Committee of the Fudan University Eye, Ear, Nose and Throat Hospital (Ethics No. 2021026), and all work was carried out in accordance with the Declaration of Helsinki.
[0045] 2. Modification of single-layer corneal stromal lens
[0046] A 1 mg / mL oxidized chondroitin sulfate (O-CS) solution was prepared, and the obtained corneal stromal lens was immersed in the O-CS solution for 2 hours, and then quickly washed in ultrapure water to remove the unabsorbed O-CS components to prepare an O-CS-modified corneal stromal lens. Some of the O-CS-modified corneal stromal lenses were placed in a 0.5 mg / mL G4 PAMAM (fourth-generation dendrimer polyamide-amine) solution for 1 hour, and quickly washed in ultrapure water to prepare a G4 PAMAM-modified corneal stromal lens.
[0047] 3. In vitro characterization of CS and G4
[0048] (1) Structural analysis and chemical properties of CS and G4 PAMAM
[0049] Infrared spectroscopy is used to examine the structure, composition, and chemical properties of CS and G4 PAMAM materials. Freeze-dried samples of CS and G4 PAMAM are prepared, fixed on a substrate, and tested in a dry state. The samples are placed in an infrared spectrometer and the spectrum of infrared radiation absorbed by the samples is recorded. Infrared spectroscopy data processing software is used to interpret the spectra, identify specific vibrational frequencies and functional groups, and thus determine the structure and composition of the macromolecules.
[0050] (2) Characterization of modified single-layer corneal stromal lenses
[0051] Chondroitin sulfate (Chs-Rho) or oxidized chondroitin sulfate (O-Chs-Rho) labeled with rhodamine B isothiocyanate was incubated with the lens for 1 hour, and washed with physiological saline to wash away the unabsorbed Chs-Rho or O-Chs-Rho. The lens was then placed in fluorescein isothiocyanate-labeled G4 PAMAM (FITC-G4 PAMAM) and incubated with the lens for 1 hour. After washing, it was observed using a laser confocal microscope (Zeiss, Germany), and the fluorescence intensity was quantitatively analyzed to compare the binding strength of Chs-Rho or O-Chs-Rho with G4 PAMAM.
[0052] The live and dead cells of the corneal tissue lens in each group under different modification conditions were detected, and the lens was stained with a live / dead kit (Dojindo Laboratorise, Japan). The skeleton protein F-actin was labeled with the fluorescent probe FITC-labeled phalloidin (ab176753, abcam, UK), and the lens was observed and photographed using a fluorescence microscope (Zeiss, Germany).
[0053] The surface morphology of the modified corneal stromal lens was observed by scanning electron microscopy (Hitachi, HITACHIBU8010). Fresh or modified single-layer corneal stromal lens was first fixed in 4wt% paraformaldehyde, dehydrated with gradient ethanol, and then placed in a critical point dryer for drying. The surface was coated with a metal coating and mounted on a 1mm×1mm conductive carbon film, and then observed under a microscope.
[0054] The morphology and electrostatic properties of the CS / G4 PAMAM-modified lenses were investigated by atomic force microscopy (AFM, Nanoscope IV MultiMode). The measurements were performed in electrostatic mode. The electrostatic properties of the lenses were evaluated using an electrostatic force microscope (EFM) module at a voltage of 0 to 5 V and a tip-to-surface distance of 25 to 100 nm. A silicon tip coated with a CoCr film (Model MESP, Veeco, Inc.) was used in the EFM mode.
[0055] (3) Stereostructure of bio-self-adhesive matrix lens with electrostatic entanglement of macromolecules
[0056] The three-dimensional structure of the bonded lens was detected by laser confocal microscopy and scanning electron microscopy. The two lenses were modified with O-CS and G4 PAMAM, respectively, and then stained with a live / dead kit (Dojindo Laboratorise, Japan). The double-layer lens was reconstructed in three dimensions using laser confocal microscopy (Zeiss, Germany) to observe its double-layer three-dimensional structure and thickness.
[0057] The three-dimensional morphological characteristics of the double-layer lens were observed by scanning electron microscopy (Hitachi, HITACHIBU8010). Two cornea superimposed samples were used, first fixed in 4wt% paraformaldehyde, dehydrated with gradient ethanol, and then placed in a critical point dryer for drying. The sample was cut into a cross-section, coated with a metal coating, and mounted on a 1mm×1mm conductive carbon film, and then observed under a microscope.
[0058] 4. Cytocompatibility
[0059] Human corneal stromal cells (HCSCs) used in the experiment were obtained from the Eye, Ear, Nose and Throat Hospital of Fudan University, China. HCSCs were cultured in DMEM / F-12 medium (Gibco, Thermo Fisher Scientific, USA) supplemented with 10% fetal bovine serum (Gibco, Thermo Fisher Scientific, USA) and an antibiotic mixture of 100 U / mL penicillin and 100 U / mL streptomycin (Gibco, Thermo Fisher Scientific, USA) at 37°C and 5% humidity. The culture medium was then aspirated and 100 μL of the culture medium plus 1 mg / mL CS, 1 mg / mL G4, 0.5 mg / mL G4, 0.25 mg / mL G4, or 0.1 mg / mL G4 was added to five replicate wells. The plates were cultured for 1, 3, and 5 days; the control group received only the culture medium.
[0060] After 1, 3, and 5 days of stimulation, the cell proliferation rate was determined using a cell counting kit-8 (CCK-8) kit (Dojindo, Japan) and a microplate reader (MK3, USA) at a wavelength of 450 nm. After 24 hours of stimulation, cell viability was assessed using a live / dead assay kit (Biotech Institute, Shanghai, China) according to the manufacturer's instructions. The morphology of HCSCs was observed using a fluorescence microscope (Zeiss, Germany).
[0061] The live and dead cells of corneal stromal cells in each group were detected by staining the lens with a live / dead kit (Dojindo Laboratorise, Japan), and observed and photographed with a fluorescence microscope (Zeiss, Germany).
[0062] Flow cytometry was used to analyze the live and dead cells of each group of treated cells and prepare single cell suspensions. Calcein AM / PI staining working solution was added to the suspension and incubated at room temperature in the dark for 15-20 minutes to allow the staining reaction to occur. Finally, the samples were placed in a flow cytometer for corresponding detection and analysis.
[0063] 5. Effect of CS / G4 PAMAM on the phenotype of corneal stromal cells
[0064] (1) Immunofluorescence detection
[0065] 4% paraformaldehyde was added to fix the cells, and PBS was added to wash the residual paraformaldehyde. Then, 0.1% PBSTX was added and the cells were incubated for 20 minutes. Then, each group of cells was blocked, and the blocking solution was prepared by 1% bovine serum albumin, 10% goat serum, 0.3M glycine (Glycine, Gly) and 0.1% PBST. After blocking for 2 hours, the primary antibody was added for overnight incubation at 4°C. Then, the secondary antibody was added to each group of cells for 1 hour, and the mounting medium containing DAPI was added, and the cells were observed and photographed under a fluorescence microscope.
[0066] (2) Cell protein immunoblotting experiment
[0067] According to the experimental grouping, the total protein of each experimental group was collected and the protein concentration was adjusted. A 10% separation gel polyacrylamide gel was prepared, and 20 μL of the sample to be tested was added to each well. SDS-PAGE electrophoresis was performed at 80V constant voltage for 0.5h. After the sample entered the separation gel, the constant voltage was 100V for 2h, and the membrane was transferred at 300mA for 2h. The sample was blocked with 10% skim milk, and the primary antibody of 1:1000 was incubated at 4℃ for 24h (GAPDH was used as a positive control), and the membrane was washed with PBS for 10min, and repeated 3 times; the secondary antibody coupled with horseradish peroxide was added, and the sample was incubated at 37℃ for 1h, and the membrane was washed with PBS for 10min, and repeated 5 times; the chemiluminescent agent was added and exposed in the dark room.
[0068] (3) RT-qPCR
[0069] Add 1mL of trizol reagent lysis buffer to the cells of different groups, let stand for several minutes, add 200μL of chloroform, let stand on ice for 15 minutes to fully react. After centrifugation, take the supernatant to another EP tube, add 500μL of isopropanol, discard the supernatant after centrifugation, add 1mL of 80% ethanol, discard the supernatant after centrifugation, dry naturally, add 20μL of DEPC water to dissolve the precipitate, and then measure the total RNA sample. According to the measured RNA concentration, calculate the required RNA volume, the required RNA is 0.1ng. Add reagents and set reaction conditions according to the instructions of the reverse transcription kit, and finally obtain cDNA. PCR uses GAPDH as the control, and we use Primer Express 3.0 software to design primer sequences (Table 1). Add 2μL cDNA, 1μL forward primer, 1μL reverse primer and 4μL SYBR to the 384-well plate. Use Real-time PCR instrument to detect it. The conditions set for real-time PCR were: first react at 50°C for 2 min, then denature at 95°C for 10 min, then denature at 95°C for 15 s, 40 cycles. Then amplify at 55°C for 30 s. Finally, add a dissociation step, react at 95°C for 15 s, react at 60°C for 15 s, and react at 95°C for 15 s. Relative gene expression levels were calculated using 2 –ΔΔCt Formula for calculation.
[0070] 6. Construction and physicochemical properties of bio-self-adhesive matrix lenses with macromolecular electrostatic entanglement
[0071] (1) Construction of bio-self-adhesive matrix lenses with electrostatic entanglement of macromolecules
[0072] A 1 mg / mL oxidized chondroitin sulfate (O-CS) solution was prepared, and the corneal stromal lens was immersed in the O-CS solution for 2 h, and then quickly washed in ultrapure water to remove the unabsorbed O-CS components. A portion of the O-CS-modified corneal stromal lens was placed in a 0.5 mg / mL G4 PAMAM solution for 1 h, and then the O-CS-modified lens and the G4 PAMAM-modified lens were superimposed and bonded.
[0073] (2) In vitro characterization of bio-self-adhesive matrix lenses with electrostatic entanglement of macromolecules
[0074] 1) Transmittance detection
[0075] A thickened untreated lens or a thickened bonded lens was placed in a 96-well plate, and the surrounding liquid was absorbed with a triangular sponge swab. The absorbance was measured using an ELISA reader (Tecan, Switzerland). The absorbance (A) was measured at a visible light wavelength ranging from 380 to 780 nm. A detection point was taken every 10 nm, and the absorbance of the sample was detected at multiple points continuously. The measurement was repeated 3 times. A blank plate was selected as a control. The transmittance (T) was calculated as follows: T = 10 -A .
[0076] 2) Adhesion test
[0077] Adhesion of two bonded corneal stromal lens samples was tested by biaxial tensile testing using a CellScale biotester (BioTester 37; CellScale, Waterloo, Canada) equipped with a 5000N load cell. The test axis was aligned with the horizontal of the lens and the specimens were connected using BioRakes. In order to ensure stability in the force-displacement curve, the stretching rate was close to 6 μm per second (strain rate = 9% / min) to ensure that the specimens were subjected to quasi-static loads. The biomechanical properties of the specimens were analyzed using stress-strain curves within a strain range of 0.06. The experiments were performed using a displacement-controlled scheme with a stretching rate close to 6 μm per second. The horizontal force and displacement were recorded to calculate the adhesion.
[0078] 7. Physicochemical characterization of G4 / puerarin complex
[0079] (1) Detection of the physicochemical characteristics of G4 PAMAM / puerarin
[0080] G4 PAMAM was dissolved in deionized water (100 mg / mL) and used as a stock solution. Puerarin was added to the G4PAMAM solution and sonicated for 2 hours to establish a stable G4 PAMAM / puerarin complex. A camera was used to record the macroscopic appearance of the puerarin suspension and the G4PAMAM complex. The absorption spectrum of the G4 PAMAM / puerarin complex was measured using a UV-visible spectrometer to confirm the formation of the G4PAMAM / puerarin complex. Transmission electron microscopy and dynamic light scattering were used to measure its physical characterization, respectively.
[0081] (2) Preparation and drug release assay of G4 PAMAM / puerarin modified lenses
[0082] The fresh lens removed during SMILE was soaked in G4 PAMAM / puerarin solution for 1 hour and then taken out. The lens was placed in a dialysis bag with 2 mL of deionized water (retained molecular weight was 1000). After sealing the dialysis bag, 1 mL of the liquid outside the dialysis bag was taken at different time points within 1 h, 2 h, 4 h, 8 h, 12 h, 24 h, 48 h, and 72 h to measure the ultraviolet absorbance value, and 1 mL of deionized water was added again. The puerarin release mass and cumulative release rate in the lens were calculated based on the measured ultraviolet absorbance value and the puerarin concentration standard curve.
[0083] (3) Effects of G4 PAMAM / puerarin nanoparticles on lipopolysaccharide (LPS)-induced corneal stromal cells
[0084] Corneal stromal cells were inoculated in 96-well plates for 12 hours, treated with LPS at a concentration of 1 μg / mL or co-cultured with LPS (1 μg / mL) and puerarin (Pue, 10, 20 and 40 μg / mL). After 24 hours of culture, cell viability was determined by MTT. RNA and protein were extracted from each group, and the expression of TNF-α, IL-6 and IL-1β in each group of cells was detected by RT-PCR and Western-blot, respectively. The specific experimental methods were the same as before.
[0085] Table 1 Primer sequences
[0086]
[0087] 8. Animal experiments
[0088] New Zealand white rabbits, weighing between 2 and 2.5 kg, were obtained from Jiagan Biotechnology Co., Ltd., China. Before the experiment, slit lamp microscopy and AS-OCT confirmed that the rabbits did not have any corneal opacity. The animal experimental procedures were strictly in accordance with the Guidelines for the Use of Animals in Ophthalmic and Vision Research provided by the Association for Research in Vision and Ophthalmology (ARVO). This study protocol was approved by the Medical Ethics Committee of the Affiliated Otolaryngology Hospital of Fudan University, China (ethics number: IACUC-DWZX-2023-037). The rabbits were randomly divided into control group, injury (Cornea defect) group, fresh thickened lens (BL) group, CS / G4 thickened lens group (BL-CS / G4) and CS / G4-puerarin thickened lens group (BL-CS / G4+PU), and one eye was selected as the experimental eye. A focal corneal epithelial and stromal defect with a diameter of 6.5 mm and a depth of approximately 1 / 3 of the full-thickness cornea was made in the central part of the cornea using a trephine combined with a curette. Each set of lenses was processed and pasted to the defect, and observation was performed immediately, 3 days, 1 week, 2 weeks and 1 month after lens implantation.
[0089] (1) In vivo observation indicators
[0090] Slit lamp microscopy was used to observe the healing of corneal stromal lens transplantation at various time points after surgery, and cobalt blue light staining was used to observe the scope of corneal defects and corneal epithelial repair. Anterior segment optical coherence tomography was used to observe the in vivo status of corneal stromal lens and the regularity of the anterior corneal surface at different time points after implantation. Corneal clarity was graded as follows: grade 0, completely transparent, no turbidity was found under slit lamp examination; grade 1, mild clouding that was difficult to observe under direct and scattered light illumination; grade 2, mild clouding that was easy to see under direct illumination; grade 3, moderately dense opacity, partially obstructing the details of the iris; grade 4, severe dense opacity, and it was completely impossible to see the intraocular structure.
[0091] (2) In vitro observation indicators
[0092] One month after surgery, the corneas of rabbits in different groups were fixed with 4% paraformaldehyde, embedded in paraffin, and then serially sliced with a thickness of about 5 μm. HE and Masson staining were performed respectively, and the arrangement of collagen fibers of the lens was observed under a light microscope. Immunofluorescence was used to observe the expression of COL1A1, a-SMA, lumican, ly6g and CD11b in the corneal tissue after transplantation. The method was the same as before.
[0093] 9. Statistical analysis
[0094] SPSS software (version 23; SPSS Inc., Chicago, IL, USA) was used for data processing and analysis. All data are presented as mean ± standard deviation (SD). Kolmogorov-Smirnov test was used to evaluate normal distribution. One-way analysis of variance (ANOVA) was used to compare data from different groups. P value < 0.05 was considered statistically significant.
[0095] 2. Experimental Results and Discussion
[0096] 1. Preparation of macromolecular modified corneal stromal lenses to achieve electrostatic entanglement bonding
[0097] The various bioactive components in the corneal stromal lens contribute to the regeneration of corneal epithelium and stroma and maintain the mechanical properties of the cornea after transplantation. In clinical practice, it can be used as a substitute for the donor cornea to treat corneal defects, corneal opacities, keratoconus and other diseases. Due to its ultra-thinness, deep corneal transplantation is currently not possible. In corneal transplantation surgery, sutures are often used to fix corneal grafts. Inspired by surgical sutures, oxidized chondroitin sulfate (O-CS) and G4 PAMAM with opposite charges are introduced on the surface of the corneal stromal lens. These two substances have a large amount of anions—SO3 - Radicals and cations—NH3 + The macromolecules form an entangled network through electrostatic interaction, forming a corneal stromal lens implant with strong cohesion and adhesion strength, achieving sutureless repair of deep corneal defects ( Figure 1 (Fig. A in the middle).
[0098] In the specific experiment, we first constructed oxidized chondroitin sulfate, and obtained aldehyde-modified chondroitin sulfate (O-CS) by oxidizing the vicinal diol on the chondroitin sulfate sugar chain with sodium periodate. We characterized chondroitin sulfate (CS) and aldehyde-modified chondroitin sulfate (O-CS) by total reflection infrared. We found that the oxidized chondroitin sulfate (O-CS) was oxidized by 1,733 cm -1 There is an obvious stretching vibration peak of C=O aldehyde group at 2847cm -1 The stretching vibration peak of the aldehyde proton C=OH at , indicating that the aldehyde group was successfully grafted onto the chondroitin sulfate molecule ( Figure 1 (Fig. B).
[0099] The fourth generation of dendritic macromolecule polyamidoamine (Generation 4polyamindoamine, G4 PAMAM) is a new type of polymer material. Its surface can be protonated under physiological conditions to form positively charged amino groups, which can interact electrostatically with negatively charged drug molecules or biological membranes. Under physiological conditions, the corneal surface is negatively charged. The corneal stroma lens is modified to be negatively charged or positively charged (O-CS) by oxidizing chondroitin sulfate (O-CS) or G4 PAMAM. Figure 1 (E), the two modified lenses non-covalently bind to the binding site on G4 PAMAM through cooperative electrostatic interactions and chondroitin sulfate as a bridge.
[0100] To verify the binding force between oxidized chondroitin sulfate and G4 PAMAM, the lens was immersed in rhodamine-labeled chondroitin sulfate (CS-Rho) or oxidized chondroitin sulfate (O-CS-Rho). Figure 1 In the middle D figure, we can see that both O-Chs-Rho and CS-Rho have an adsorption effect on the lens, and the fluorescence intensity of O-Chs-Rho is significantly higher than that of Chs-Rho (P=0.0003), indicating that O-CS has a stronger adsorption effect on the lens. The two groups of lenses after staining were then immersed in FITC-labeled G4PAMAM. Figure 1 The results of the middle D figure show that the FITC fluorescence intensity of the O-CS-Rho group was significantly higher than that of the Chs-Rho group (P=0.0015), indicating that O-CS has a stronger binding force with G4 PAMAM. Figure 1 The middle G image is a side view of the bonded corneal lens observed by SEM. It can be seen that the two layers of the lens are tightly bonded without obvious gaps, the dividing line is visible, and the lens collagen is neatly arranged. Figure 1The scanning electron microscope of the middle G image shows that there is no obvious change in the surface of the corneal stromal lens after O-CS modification compared with the control group. Both groups show brush-like irregular structures and discontinuous collagen fibers. The surface of the corneal stromal lens modified by O-CS / G4 PAMAM is smoother than that of the control group because G4 has a cross-linking effect on the collagen inside the corneal stromal lens. In summary, these results characterize the electrostatic modification of the lens surface by macromolecules in in vitro experiments, and good adhesion is observed between the modified lenses through electrostatic entanglement at the macroscopic and microscopic levels.
[0101] 2. In vitro biocompatibility testing of macromolecules
[0102] Macromolecules used to modify corneal stromal lenses need to have good biocompatibility. Live / dead and flow cytometry were used to evaluate the effects of O-CS and G4 on the activity, proliferation, and apoptosis of corneal stromal cells. Figure 2 Live / dead staining in panel A shows that these cells have high viability (>90%) and almost no dead cells were detected after 1 day of O-CS and G4 stimulation, indicating cell growth and proliferation. Figure 2 The results of PI staining detected by flow cytometry in the middle B figure showed that compared with the control group, there was no significant difference in the proportion of PI-positive cells among the different treatment groups, the proportion of positive cells was lower, and the cell apoptosis rate was lower. The results of immunofluorescence staining, qPCR and Western blot analysis showed that the keratinocyte markers keratinocytes, Lumican and ALDH3A1 were highly expressed, but fibronectin (FN) and α-SMA were lowly expressed. There was no significant difference in the O-CS and CS / G4 treatment groups compared with the control group ( Figure 2 (see Figure CF in the figure).
[0103] These experimental results show that O-CS and G4 have good biocompatibility and have no significant effect on cell phenotype. In summary, these results prove that the biomacromolecules used for electrostatic modification have good biocompatibility.
[0104] 3. Biological properties and adhesion test of bio-self-adhesive matrix lenses with macromolecular electrostatic entanglement
[0105] Introducing the macromolecular electrostatic entanglement theory into the preparation of biological self-adhesive matrix lenses requires precise design of materials. By regulating the molecular structure and charge distribution, the self-adhesion of corneal matrix lenses can be achieved, and a balance can be achieved between material properties (such as transmittance, adhesion, etc.) and biocompatibility. First, the transmittance of the lens is tested using a camera and an ELISA instrument. Figure 3As can be seen in Figure A, there is no significant difference in the transmittance of the lens with increasing CS concentration. When the CS concentration is constant, the transmittance of the lens gradually decreases with the increase of G4 PAMAM concentration. When CS with a concentration of 1 mg / mL is combined with 1 mg / mL G4PAMAM, the transmittance is significantly lower than that of the control group (P=0.002). When CS with a concentration of 1 mg / mL is combined with 0.5 mg / mL G4PAMAM, the transmittance is not significantly different from that of the control group (P=0.56), and the transmittance is significantly better than that of the commercial product fibrin glue (P<0.0001). The transmittance of the cornea depends on the appropriate diameter and spacing of collagen fibers. However, as the concentration of G4 PAMAM increases, the transmittance of the lens gradually decreases due to its cross-linking effect on the collagen.
[0106] The results of adhesion showed that ( Figure 3 (E), when the CS concentration is constant, the adhesion between the two lenses gradually increases with the increase of G4 PAMAM concentration. When CS with a concentration of 1 mg / mL is combined with G4 PAMAM with a concentration of 1 mg / mL, the adhesion (33.80±2.12 kPa) is not significantly different from that of commercial fibrin glue (P=0.54). When CS with a concentration of 1 mg / mL is combined with G4 PAMAM with a concentration of 0.5 mg / mL, the adhesion is significantly lower than that of commercial fibrin glue (P<0.0001), but significantly higher than that of the control group and 0.25 mg / mL G4 PAMAM and 0.5 mg / mL G4 PAMAM under the condition of 1 mg / mL CS (P<0.0001). CS / G4 PAMAM-Pu modified corneal stroma lenses are easy to prepare. In the case of taking into account both transmittance and adhesion, 1 mg / mL CS and 0.5 mg / mL G4 PAMAM were selected as the action concentrations in subsequent experiments. Therefore, the adhesive force between corneal stroma lenses generated by electrostatic entanglement can meet the actual needs of sutureless fixation of implants in clinical practice, and can prepare self-adhesive stroma lenses with a certain thickness.
[0107] Dye the lens with dead-live dye and observe the thickness of the lens in the 3D imaging image. Figure 3 The B part of the figure shows that the thickness of the single-layer lens is about 80 microns, and the thickness of the double-layer lens after bonding is about 160 microns. The results of dead-live staining show that compared with the control group ( Figure 3 (C), the proportion of live corneal stromal cells modified by O-CS (P = 0.92) or CS / G4PAMAM (P = 0.98) was not significantly different from that of the control group. The results of phalloidin staining ( Figure 3(D) The fluorescence intensity of corneal stromal cells modified with O-CS (P = 0.64) or CS / G4 PAMAM (P = 0.08) was not significantly different from that of the control group. The above results all indicate that O-CS and G4 PAMAM have high biocompatibility with corneal stromal lenses. In summary, these results prove that the bio-self-adhesive stromal lens with macromolecular electrostatic entanglement has good adhesion, can form a bio-self-adhesive stromal lens with macromolecular electrostatic entanglement, and has good light transmittance and biological activity.
[0108] 4. Drug loading capacity and characterization of G4 PAMAM
[0109] In order to endow the corneal stromal lens with the function of inhibiting early inflammatory response and promoting post-traumatic repair, we encapsulated the anti-inflammatory drug Puerarin in the dendritic macromolecule G4 PAMAM to form G4 PAMAM-Pu, which significantly improved the solubility of Puerarin. Puerarin can inhibit the early acute inflammatory response after surgery and inhibit the expression of proliferation-related cytokines such as NF-κb and TGF-β1. However, Puerarin is a fat-soluble drug, which diffuses slowly in body fluids and has poor effect when used topically. The use of dendritic macromolecules can encapsulate the drug in its internal pores and form nanoparticles with the drug, thereby significantly improving the solubility of the drug. Macroscopically, Puerarin is a white turbid suspension, which turns into a transparent aqueous solution after the addition of G4 PAMAM. Therefore, G4 PAMAM promotes the dissolution of Puerarin ( Figure 4 SEM images show that G4 PAMAM and G4 PAMAM-Pu composites are indeed spherical ( Figure 4 B). According to the DLS results, the average particle sizes of G4 PAMAM and G4 PAMAM-Pu were 7.0±2.65nm and 160.0±10.0nm, respectively ( Figure 4 The average Zeta potentials of G4 PAMAM and G4 PAMAM-Pu were 13.80±0.66mV and 43.17±2.75mV, respectively ( Figure 4 The UV-visible absorption spectrum shows that G4PAMAM-Pu has an independent wave different from the G4 PAMAM wave and the Pu wave, indicating that G4 PAMAM forms an independent G4 PAMAM-Pu complex after absorbing puerarin, which changes the solution wavelength from 320nm (Pu) to 350nm (G4 PAMAM-Pu) ( Figure 4 (Fig. E).
[0110] The drug release rate of G4 PAMAM-Pu was studied by dialysis bag release test. Pu with a smaller molecular weight can enter the external solution through the dialysis bag, while G4 PAMAM with a larger molecular weight is retained in the bag. Within 12 hours, more than 80% of Pu dissociated from G4 PAMAM, indicating that after Pu combines with G4PAMAM, due to the increased solubility of Pu and being encapsulated in G4 PAMAM, it can be gradually released into the solution, which can play a sustained release effect compared with the simple dissolved Pu ( Figure 4 The positive amino charge on the surface of G4 PAMAM can strengthen the contact with the negatively charged cell membrane, promote the G4 PAMAM-Pu complex to enter the cell and release the puerarin contained in it to exert its pharmacological effect; in addition, studies have shown that this type of dendrimer can reduce the intracellular clearance rate of drugs and prolong the duration of drug action, further confirming the superiority of G4 PAMAM as a drug carrier.
[0111] In the in vitro experiment, a series of puerarin concentrations were used to stimulate corneal stromal cells to observe its effect on the proliferation of corneal stromal cells. Figure 4 The results of the middle G sub-graph show that there is no significant difference between each concentration group and the control group, indicating that puerarin has good cell compatibility. Under the condition of LPS stimulation, the results show that compared with the LPS group, as the concentration of puerarin increases, its ability to enhance the proliferation activity of corneal stromal cells is stronger. Under the stimulation of LPS, 40μM puerarin has no significant difference compared with the control group (P=0.08), and the proliferation activity is significantly increased compared with the LPS group (P<0.0001). Through the above experiments, 40μM puerarin was selected for subsequent experiments ( Figure 4 We found that after LPS induction, the expression levels of inflammatory factors IL-6, TNF-a and IL-1β were significantly increased compared with the control group. After Pu treatment, the expression of IL-6, TNF-a and IL-1β was significantly decreased compared with the LPS group ( Figure 4 The results showed that Pu could inhibit the inflammatory response of corneal stromal cells induced by LPS.
[0112] In summary, these results prove that the self-adhesive corneal stroma module based on electrostatic entanglement can encapsulate and locally release drugs, inhibit inflammatory response and promote damage repair. On this basis, we will use the drug-encapsulated corneal stroma module to repair deep corneal stroma defects.
[0113] 5. Evaluation of the efficacy of bio-self-adhesive matrix lens with macromolecular electrostatic entanglement in the treatment of corneal defects
[0114] To further evaluate the ability of the self-adhesive stromal lens to repair deep corneal defects, an in vivo study was conducted using a rabbit corneal lamellar excision model. A corneal anterior lamellar defect model (6 mm in diameter and approximately 1 / 3 of the anterior stroma) was created using a trephine in New Zealand white rabbits, and then the CS / G4-Pu lens was attached to the defect without suturing. Two fresh corneal stroma lenses and CS / G4 modified posterior lens implants were used as control groups, and untreated wounds were used as negative controls.
[0115] Figure 5 Figure A in the middle shows the corneal tissue reaction and epithelialization progress after different treatment times. Within 1 month after surgery, the rabbit cornea was observed by conventional optics and fluorescein staining under a slit lamp microscope at different time points. Three days after surgery, no transplanted double-layer corneal lens graft was observed in the BL group, while the transplanted thickened corneal stromal lens graft could still be observed in the BL-CS / G4 group and the BL-CS / G4 Pu group. From the slit lamp images, it can be seen that in the observation one month after surgery, the cornea of the BL-CS / G4Pu group remained transparent, while the other groups showed corneal opacity to varying degrees. The results of corneal transparency grading evaluation showed that three days after surgery, the transparency of the BL-CS / G4-Pu group was significantly better than that of the negative control group (P=0.03), the BL group (P=0.003) and the BL-CS / G4 group (P=0.01). The results one month after surgery showed that the BL-CS / G4-Pu group was almost completely transparent, and the transparency was significantly better than the other three groups (P<0.0001)( Figure 5 (D in the middle).
[0116] Fluorescence images were taken under a slit lamp using a cobalt blue filter at different time points, with green showing areas where the epithelium had not yet fully healed. The results showed that the size of the corneal epithelial defect in each group gradually decreased over time. On the third day after surgery, the degree of epithelialization in the CS / G4-Pu group was better than that in the other groups. Compared with the negative control group, the BL-CS / G4-Pu group significantly accelerated the healing of the corneal wound (P<0.0001). Figure 5 As shown in the middle B figure, on the 7th day after transplantation, the wounds in the BL-CS / G4-Pu group were almost completely healed, while the wound healing rates in the negative control group, BL group, and BL-CS / G4 were 72.50%, 77.50%, and 82.50%, respectively ( Figure 5 The corneal defect repair process at different time points after surgery was recorded by anterior segment optical coherence tomography (AS-OCT). Figure 5C in the middle), a clear boundary between the implant and the host tissue was observed in all groups immediately after surgery, and the implant adapted well to the curvature of the corneal stromal bed. On the third day after surgery, no corneal lens implant was observed in the BL group, and there was no significant difference in corneal thickness between the BL group and the negative control group (P=0.66). The corneal thickness of the BL-CS / G4 group and the BL-CS / G4-Pu group was significantly higher than that of the other groups (P<0.0001). Three days after surgery, a thin layer of white tissue membrane was observed on the outer surface of the lens in the CS / G4-Pu group in the OCT image, indicating the formation of an epithelial layer, which was consistent with the observation results of fluorescent staining under cobalt blue light. In the observation one month after surgery, the degree of epithelialization in the CS / G4-Pu group was significantly higher than that in the CS / G4 group, and there was no significant difference in corneal thickness between the two groups (P=0.17)( Figure 5 In summary, these results demonstrate that the bio-self-adhesive matrix lens modified with macromolecules can be transplanted without sutures. Through the electrostatic entanglement between macromolecules, the lens has good inter-tissue adhesion and repair effect.
[0117] 6. Bio-self-adhesive matrix lenses with macromolecular electrostatic entanglement inhibit postoperative inflammatory response and promote repair
[0118] H&E and Masson staining of corneal tissue samples showed the wound healing reaction process of corneal epithelium and stroma one month after surgery. One month after surgery, it was observed that all groups had completed epithelialization, and the regenerated epithelial tissue was similar to the healthy cornea in shape and thickness. In addition, no new blood vessels were found in the CS / G4-Pu group or the CS / G4 group, indicating that the modified corneal stroma lens had good ocular tissue compatibility. As shown in Figures a and b, the thickened corneal stroma lens in the CS / G4-Pu group or the CS / G4 group adhered well to the corneal receptor stroma bed, and the corneal defect was completely repaired by the thickened lens graft, but no corneal lens graft was found in the BL group. The tissues in the BL-CS / G4-Pu group were arranged neatly and tightly compared with the BL-CS / G4 group, and there were no large number of cavitation bubbles between the tissues, and the tissues were tightly adhered to the epithelium.
[0119] Healing after corneal epithelial stromal defects has clear stage healing, and the complex cascade reaction depends on the interaction of proteases and their inhibitors to achieve appropriate ECM remodeling. The first stage of wound healing is the recruitment of resident leukocytes to the site of injury, which affects the cell behavior during wound healing and serves as a source of cytokine and growth factor production. Subsequently, corneal epithelial cells migrate along the stromal bed, and leukocytes disappear when the epithelium covers. After re-epithelialization, compensatory epithelial hyperplasia occurs. A series of pathological problems regarding the healing of corneal defects can be solved by reducing the expression of inflammatory factors and inhibiting fibroblast activation. Puerarin can inhibit early postoperative inflammatory reactions and inhibit the expression of TGF-β1, etc. Ly6G mainly marks and identifies neutrophils, and CD11b is used to mark a variety of immune cells, including monocytes (monocytes include monocytes, macrophages, and dendritic cells), both of which are related to tissue inflammatory responses. The results of immunofluorescence staining showed that the expression of Ly6g in the BL-CS / G4 Pu group was significantly lower than that in the cornea defect group (P<0.0001), BL group (P<0.0001) and BL-CS / G4 group (P<0.0001).
[0120] The expression of CD11b in the BL-CS / G4 Pu group was also significantly lower than that in the cornea defect group (P=0.003), BL group (P=0.02) and BL-CS / G4 group (P=0.0006), indicating that early postoperative sustained-release puerarin effectively inhibited the expression of inflammatory-related factors.
[0121] Lumican is an important corneal proteoglycan that is not only involved in the regulation of collagen structure and function, but also plays a vital role in maintaining corneal transparency. Previous studies have shown that when Lumican is knocked out in mice, corneal opacity continues to form, and corneal opacity in Lumican-deficient mice progresses with age. Our immunofluorescence staining results showed that compared with the normal control group, the expression of Lumican in the cornea defect group (P<0.0001), BL group (P<0.0001) and BL-CS / G4 group (P<0.0001) was significantly decreased, but there was no significant difference between the BL-CS / G4 Pu group and the control group (P=0.07), indicating that the CS / G4-Pu modified corneal stroma lens has good transparency after transplantation.
[0122] α-SMA is α-smooth muscle actin, and COL1A1 is a myofibroblast marker, collagen I. Immunofluorescence staining of the two was performed to analyze the presence of myofibroblasts and corneal stromal fibrosis. The results of COL1A1 immunofluorescence quantitative analysis showed that there was no significant difference between the BL-CS / G4 Pu group and the control group (P=0.99). The results of α-SMA staining showed that the expression of the corneadefect group (P=0.04), BL group (P=0.0007) and BL-CS / G4 group (P<0.0001) was significantly decreased compared with the control group, while there was no significant difference between the BL-CS / G4 Pu group and the control group (P=0.85). The results of in vivo animal studies showed that the negative expression of α-SMA indicated that the differentiation of keratinocytes into myofibroblasts was inhibited, thereby inhibiting the fibrotic reaction. The results of in vivo studies showed a good corneal repair effect in the short term, but the long-term effect is still unclear. Longer follow-up studies will help determine the durability and safety of macromolecular modified bioadhesive matrix lenses in long-term use.
[0123] Conclusion
[0124] In this study, we innovatively constructed a self-adhesive thickened corneal stroma module for sutureless corneal lens transplantation. We used macromolecules with opposite charges, oxidized chondroitin sulfate (O-CS) and G4PAMAM to modify the corneal stroma lens. Through the electrostatic entanglement of macromolecules, we achieved customized thickening of the corneal stroma lens and sutureless fixation to repair deep corneal stroma defects. It can also encapsulate and locally release drugs, playing the additional function of inhibiting postoperative inflammatory response and promoting repair. Studies have shown that the corneal stroma module has good adhesion, transmittance and cell activity. In addition, the matrix module was applied to New Zealand rabbit anterior lamellar corneal transplantation. The postoperative corneal graft had good fixation, could promote rapid epithelialization, and was well integrated with the matrix without showing obvious scar formation or immune response. In short, the corneal stroma module is a very promising bioactive material for corneal repair. Its wide source, suture-free, inflammation-reducing and repair-promoting characteristics provide new ideas for living tissue transplantation or wound repair.
[0125] Comparative Example 1
[0126] According to the testing method of Example 1, the two obtained corneal stromal lenses were directly stacked and bonded without any treatment. A total of 10 groups of samples were selected for testing. The adhesion between the two fresh and untreated corneal stromal lenses was measured to be 0.1-0.4 kPa, indicating that the adhesion between the two corneal stromal lenses that have not undergone surface modification treatment is extremely weak.
[0127] Comparative Example 2
[0128] According to the test method of Example 1, the corneal stromal lens modified with G4 PAMAM and the corneal stromal lens modified with chondroitin sulfate were superimposed and bonded, and the adhesion force between the two was tested to be 2.11±1.08 kPa, indicating that the corneal stromal lens modified with chondroitin sulfate and the corneal stromal lens modified with G4 PAMAM could not form a macromolecular electrostatic entanglement network, resulting in extremely weak adhesion between the two.
[0129] Comparative Example 3
[0130] According to the test method of Example 1, the corneal stromal lens was modified with G4 PAMAM and then with hyaluronic acid-methacrylate (HA-MA), and the two were superimposed and bonded. The obtained adhesion force was 11 kPa and the transmittance was 63%.
[0131] Comparative Example 4
[0132] According to the test method of Example 1, G4 PAMAM was modified with methacrylate groups and then grafted onto the surface of the corneal stromal lens. Then, the corneal stromal lens was modified with hyaluronic acid modified with sulfhydryl groups. The two were superimposed and bonded. The obtained adhesion was 20 kPa and the transmittance was 67%.
Claims
1. A method for preparing a sutureless bio-self-adhesive matrix lens to thicken the cornea, characterized in that: The following steps are involved: (1) soaking a corneal stromal lens in an oxidized chondroitin sulfate solution to obtain an oxidized chondroitin sulfate-modified corneal stromal lens; (2) treating another corneal stromal lens by immersing it in a fourth-generation dendrimer polyamide-amine solution to prepare a G4PAMAM-modified corneal stromal lens; (3) The two corneal stromal lenses obtained in step (1) and step (2) are stacked to achieve self-adhesion through the electrostatic entanglement reaction between molecules, thereby obtaining the seamless biological self-adhesive stromal lens thickened cornea.
2. The preparation method according to claim 1, characterized in that: The concentration ratio of the oxidized chondroitin sulfate to the fourth-generation dendrimer polyamide-amine is 2:
1.
3. The preparation method according to claim 1, characterized in that: The concentration of the oxidized chondroitin sulfate solution in step (1) is 1 mg / mL.
4. The preparation method according to claim 1, characterized in that: The concentration of the fourth generation dendrimer polyamide-amine solution in step (2) is 0.5 mg / mL.
5. The preparation method according to claim 1, characterized in that: The source of the corneal stromal lens is the discarded corneal stromal lens which is medical waste generated by femtosecond laser small incision corneal stromal lens removal surgery.
6. The preparation method according to claim 1, characterized in that: The oxidized chondroitin sulfate is prepared by treating chondroitin sulfate with sodium periodate.
7. A cornea thickening method using a sutureless bio-self-adhesive matrix lens obtained by the preparation method according to any one of claims 1 to 6.
8. The sutureless bio-self-adhesive matrix lens for corneal thickening according to claim 7, characterized in that: Its thickness is 100-400 μm.
9. The sutureless bio-self-adhesive matrix lens for thickening the cornea according to claim 7, characterized in that: Its light transmittance is 70-73%.
10. Use of the seamless bio-self-adhesive matrix lens thickened cornea obtained by the preparation method according to any one of claims 1 to 6 or the seamless bio-self-adhesive matrix lens thickened cornea according to any one of claims 7 to 9 as a corneal tissue engineering material.
Citation Information
Patent Citations
Corneal lamellar piece and production method thereof
CN103892938A
Dendrimer-bioadhesive polymer hydrogel nanoglue and use thereof
CN108883207A